The rise and fall of Serial Verb Constructions: Finale - Andrason, Alexander; Aikhenvald, Alexandra Y.; Egbokhare, Francis O.; Fehn, Anne-Maria; Gębka-Wolak, Małgorzata; Locatell, Christian; Lovestrand, Joseph; Moroz, Andrzej; Nau, Nicole; Phiri, Admire; Pratchett, Lee J.; Ross, Daniel; et al. (Stellenbosch Papers in Linguistics Plus, 2022)
This article concludes the special issue of Stellenbosch Papers in Linguistics PLUS dedicated to the diachrony of Serial Verb Constructions. The authors of the ten contributions included in the volume discuss the most important results of their studies and suggest the possible lines for future research.